Analisis Swelling Clay di Formasi Telisa Untuk Perencanaan Lumpur Pemboran Skala Laboratorium - Nugroho Marsiyanto; Abdullah Rizky Agusman; Faqqih Badruzzaman (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2023)
In the exploration stage, there is a well drilling operation process aimed at making holes in locations identified as having oil/gas. At the time of the drilling, it does not always run well so that it can cause problems that interfere with drilling operations such as swelling clay, sloughing shale, caving shale, and differential pipe sticking which may be due to the formation lithology penetrating thick shale formations, so that these problems can slow the penetration rate and increase the cost of drilling operations. Then the swelling clay analysis was carried out to overcome this problem. This study aims to determine the reactivity of cuttings by identifying the clay content in the Telisa Formation and planning the drilling mud to be used, so that it is suitable if it penetrates the Telisa Formation so that clay Swelling does not occur. There are 3 different types of water base mud, namely 7% KCL Polymer PHPA, 7% KCL Polymer Polyamine, and 7% KCL Polymer Soltex. This method is carried out in a laboratory test by conducting several Density, Yield Point, Plastic Viscosity, Gel Strength, MBT (Methylene Blue Test) and LSM (Linear Swelling Meter) tests. The results of the 7% KCl Polymer PHPA mud test were Density 9.9 ppg, Plastic Viscosity 20 cp, Yield Point 18 lb/100 ft2, MBT 15 meq, and LSM 29.5 meq/100 gr. In the 7% KCl Polymer Polyamine mud test, namely Density 9.8 ppg, Plastic Viscosity 19 cp, Yield Point 18 lb/100 ft2, MBT 12.5 meq, and LSM 24.375 meq/100 gr. In the 7% KCl Polymer Soltex mud test, namely Density 9.7 ppg, Plastic Viscosity 20 cp, Yield Point 17 lb/100 ft2, MBT 10 meq and LSM 19.5 meq/100 gr. There are different values on the properties of the mud in each test using 3 different types of additives.